2007
DOI: 10.1107/s0108768107015583
|View full text |Cite
|
Sign up to set email alerts
|

Crystal chemistry of borates: the classification and algebraic description by topological type of fundamental building blocks

Abstract: The structural characteristics of all the borates available were analyzed using the Inorganic Crystal Structure Database. The fundamental building blocks (FBBs) in 841 borates were systematically classified into 6 types in terms of their topological structures. By including the polymerization of the FBBs in the borate structure, a novel systematic classification and an algebraic description of borates have been proposed. The current systematic borate classification, in which all the identical FBBs can be class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 32 publications
2
68
0
Order By: Relevance
“…It was shown that the frequency of occurrence for borate anions in 460 anhydrous borates [35] is the following: isolated triangles and tetrahedra-52%, layers-15%, frameworks-12%, finite B-O groups-12%, infinite chains-9%. The distribution of boron-oxygen [35] and 841 hydrous and anhydrous borates, respectively [30]. It was shown that the frequency of occurrence for borate anions in 460 anhydrous borates [35] is the following: isolated triangles and tetrahedra-52%, layers-15%, frameworks-12%, finite B-O groups-12%, infinite chains-9%.…”
Section: Occurrence Of B-o Polyanions Of Different Dimensionalitymentioning
confidence: 99%
See 4 more Smart Citations
“…It was shown that the frequency of occurrence for borate anions in 460 anhydrous borates [35] is the following: isolated triangles and tetrahedra-52%, layers-15%, frameworks-12%, finite B-O groups-12%, infinite chains-9%. The distribution of boron-oxygen [35] and 841 hydrous and anhydrous borates, respectively [30]. It was shown that the frequency of occurrence for borate anions in 460 anhydrous borates [35] is the following: isolated triangles and tetrahedra-52%, layers-15%, frameworks-12%, finite B-O groups-12%, infinite chains-9%.…”
Section: Occurrence Of B-o Polyanions Of Different Dimensionalitymentioning
confidence: 99%
“…Becker in 2001 as well as Guan and Xue in 2007 examined how often B-O polyanions of different dimensionality (the degree of polymerization-0D, 1D, 2D, 3D) do occur in 460 anhydrous [35] and 841 hydrous and anhydrous borates, respectively [30]. It was shown that the frequency of occurrence for borate anions in 460 anhydrous borates [35] is the following: isolated triangles and tetrahedra-52%, layers-15%, frameworks-12%, finite B-O groups-12%, infinite chains-9%.…”
Section: Occurrence Of B-o Polyanions Of Different Dimensionalitymentioning
confidence: 99%
See 3 more Smart Citations